2007
DOI: 10.1177/0148607107031005397
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotics Attenuate Bowel Segment Reversal–Induced Systemic Inflammatory Response and Body Weight Loss in Massively Bowel‐Resected Rats

Abstract: Our results suggest that oral antibiotics may be used as an adjuvant to attenuate the inflammatory responses and to enhance the anabolic responses in massively bowel-resected patients with bowel segment reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our previous study showed that small bowel segment reversal stimulates jejunal hyperplasia but may increase the possibility of bacterial translocation, which induces the inflammatory responses. 14,24 Other studies indicated that bacterial translocation significantly depressed the mitogenic response of systemic lymphocytes 5,25 and elevated the intestinal immune response. 6,9 In this study, we observed that bowel segment reversal significantly decreased subpopulation distribution of suppressor-and immature-T cells, increased numbers of NK cells (NKR-P1A+CD3-), that is, cells mainly driven from the spleen to destroy the viral-or bacterial-infected cells in the circulation, 15 and elevated ratio of helper-and suppressor-T cells in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study showed that small bowel segment reversal stimulates jejunal hyperplasia but may increase the possibility of bacterial translocation, which induces the inflammatory responses. 14,24 Other studies indicated that bacterial translocation significantly depressed the mitogenic response of systemic lymphocytes 5,25 and elevated the intestinal immune response. 6,9 In this study, we observed that bowel segment reversal significantly decreased subpopulation distribution of suppressor-and immature-T cells, increased numbers of NK cells (NKR-P1A+CD3-), that is, cells mainly driven from the spleen to destroy the viral-or bacterial-infected cells in the circulation, 15 and elevated ratio of helper-and suppressor-T cells in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…13 Also, when orally administered with antibiotics such as clindamycin and amoxicillin, the segment reversal-induced body weight loss and systemic inflammatory responses were significantly attenuated in rats with massive bowel resection. 14 It has been reported that animals and patients with massive bowel resection have elevated proinflammatory cytokines in the circulation, such as tumor-necrosis factor (TNF)-α and interleukin (IL)-6; declined expression of T-helper (Th) 1 cytokines in intraepithelial lymphocytes, such as IL-2 and interferon (IFN)-γ; and impaired proliferation response in T-cells. 1,15 Rats with massive bowel resection also had preserved humoral immunity and redistributed lymphocyte subsets.…”
Section: 2 Suchmentioning
confidence: 99%
See 2 more Smart Citations
“…Some microbial modifiers—antibiotics and probiotics—fail to balance gut adaption and liver health when treating IFALD. Broad‐spectrum antibiotics successfully ameliorated liver inflammation and steatosis in SBS animals, 142 but reduced gut adaption 142,143 . Probiotics and prebiotics (Table 2) improved gut adaption and gut barrier function in SBS animals and patients in most studies 144‐153 with several showed no significant improvement 154,155 ; but many probiotics used in these studies encode bsh genes, such as Lactobacillus johnsonii and Bifidobacterium breve .…”
Section: The Ba‐gm Axis and Clinical Management Of Ifaldmentioning
confidence: 99%